A Novel Cortex Phellodendri Chinensis–Based Carbon Dots Platform for Remarkable Analgesia for Clinical Pain Management - Huimin Peng; Xingxing Zeng; Songbai Li; Xin Wang (Veterinary Medicine and Science)
ABSTRACT In this study, we explored the eco‐friendly synthesis of photoluminescent CCDs employing a direct one‐step pyrolysis process, utilizing natural Cortex Phellodendri Chinensis as the precursor material and studied their analgesic effect in mice. The synthesized carbon dots underwent comprehensive characterization through a range of spectroscopic and microscopic techniques. These included UV‐Vis, FTIR, fluorescence spectroscopy and HR‐TEM, DLS instruments. HR‐TEM results exhibited the presence of homogenous spherical‐shaped C‐dots of about 3.3 nm without aggregates. Furthermore, the prepared CCDs were studied for their in vivo analgesic effect in mice by performing tail‐immersion, hot plate and acetic acid writhing tests. Also, an MTT assay was performed to assess the in vitro cytotoxicity of CCDs against L929 cells. In vitro cytotoxicity studies revealed that L929 cells exhibited higher cell viability when treated with prepared CCDs. The cellular uptake studies revealed the phase contrast images of MG‐63 cells at wavelength 488 nm clearly depicted the aggregation of green, fluorescent CCDs within the cells while leaving nuclei unobscured. In addition, to the best of our understanding, the results presented in this paper showed that CCDs exhibited an important analgesic effect and enhanced anti‐nociceptive activity, which may be due to stimulation of the opioidergic system. Consequently, CCDs appear to be a viable analgesic alternative for traditional analgesic candidates in pain management.